IC 8435 Grace Mine Iron Ore Waste Disposal System And Estimated Costs - William Cochran (The National Institute for Occupational Safety and Health (NIOSH), 1969)
The mineral waste disposal system at the Grace Mine, Morgantown, Pa., was designed to minimize environmental effects while allowing much of the waste from the iron mine, mill, and concentrator to be utilized. Standard cost estimating procedures were used by the Bureau of Mines to determine waste disposal costs. Mill tailings and rock waste disposal costs were estimated at $0.151 and $0.276 per ton, respectively, for the 1965-67 production period. Total waste disposal cost was reduced about $0.015 per ton by utilizing part of the waste as aggregate. The net average cost for disposal of all mineral waste was $0.189 per ton.